Pengaruh Perceived Organizational Support, Reward, Dan Budaya Organisasi Terhadap Kinerja Karyawan Dengan Pemediasi Employee Engagement - Adji Sadewo, Setyo; Soni Kurniawan, Ignatius (Akmenika: Jurnal Akuntansi dan Manajemen, 2024)
This study aims to examine the effect of perceived organizational support, rewards, and organizational culture on employee performance by mediating employee engagement among The Hotel Victoria Yogyakarta employees. This research is a quantitative study with a population of The Hotel Victoria Yogyakarta employees. A total of 40 employees whose data was collected using a census questionnaire. Data were analyzed using the SPSS version 23 software application, including multiple linear regression tests and Sobel tests. The results of this study indicate that perceived organizational support and reward have no significant effect on employee performance. Organizational culture has a significant effect on employee performance. Perceived organizational support, rewards, organizational culture, and employee performance have no significant effect on employee engagement. The implications of the research results are discussed in the discussion section.